2015
DOI: 10.1021/acs.bioconjchem.5b00081
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Iminosugars Improve the Activity of Carbohydrate-Processing Enzymes

Abstract: Multivalent iminosugars have recently emerged as powerful tools to inhibit the activities of specific glycosidases. In this work, biocompatible dextrans were coated with iminosugars to form linear and ramified polymers with unprecedently high valencies (from 20 to 900) to probe the evolution of the multivalent inhibition as a function of ligand valency. This study led to the discovery that polyvalent iminosugars can also significantly enhance, not only inhibit, the enzymatic activity of specific glycoside-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
(47 reference statements)
1
35
0
Order By: Relevance
“…Clustering of inhibitory moieties (inhitopes) on multivalent scaffolds has been shown to inhibit glycosidases with high potency. 1930 Use of the GlcNS(6S) α (1,4)GlcA disaccharide is also advantageous, as it does not contain an iduronic acid unit nor a C(3)-sulfated glucosamine, diminishing cross-bioactivity. 43,5962 Furthermore, we hypothesize that attachment of this disaccharide to the aglycon polymerizable linker, which disrupts the hydrolytic ability of heparanase and provides π -cation interactions if an aromatic system is employed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clustering of inhibitory moieties (inhitopes) on multivalent scaffolds has been shown to inhibit glycosidases with high potency. 1930 Use of the GlcNS(6S) α (1,4)GlcA disaccharide is also advantageous, as it does not contain an iduronic acid unit nor a C(3)-sulfated glucosamine, diminishing cross-bioactivity. 43,5962 Furthermore, we hypothesize that attachment of this disaccharide to the aglycon polymerizable linker, which disrupts the hydrolytic ability of heparanase and provides π -cation interactions if an aromatic system is employed.…”
Section: Resultsmentioning
confidence: 99%
“…However, to the best of our knowledge, the use of synthetic polymers have yet to be fully explored. 19,20,30 …”
Section: Introductionmentioning
confidence: 99%
“…The most significant effect was obtained with HexAB with Rp/ n values of 131, 32, and 75 observed for compounds 20 , 21 , and 22 with increasing valency of 2, 4, and 8, respectively. Previously, several studies have found that higher valency does not necessarily correlate with improved multivalent binding avidity for targeted carbohydrate‐binding or carbohydrate‐processing proteins . To improve potency, fine tuning of the spatial distribution of the azepane ligands through altering the scaffold may be a more effective strategy than simply increasing multivalency.…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, a very recent study demonstrated that polymeric iminosugars could improve the enzymatic activity of some glycosyl-hydrolases, and thus act as effectors, not inhibitors. 9 To date, the glycosidase family is the enzyme class for which the largest amount of data on MEI is available. 6,7,9,10 First, it can be concluded that, among all glycosidases assayed, a minority could be inhibited with a significant multivalent effect.…”
Section: Introductionmentioning
confidence: 99%
“…9 To date, the glycosidase family is the enzyme class for which the largest amount of data on MEI is available. 6,7,9,10 First, it can be concluded that, among all glycosidases assayed, a minority could be inhibited with a significant multivalent effect. Second, MEI seems to be extremely sensitive to the structure of the multimeric inhibitor: the topology, the valency, the structure of the central scaffold and the length/ rigidity of the tether to which each inhibitor is grafted to the scaffold are parameters that need to be fine-tuned in order to observe and optimize a multivalent inhibition.…”
Section: Introductionmentioning
confidence: 99%